Possible Assessment of Calf Venous Pump Efficiency by Computational Fluid Dynamics Approach - Niccolini, Gianni; Manuello, Andrea; Capone, Antonio; Marongiu, Giuseppe; Dell’Osa, Antonio Hector; Fois, Andrea; Velluzzi, Fernanda; Concu, Alberto (Frontiers in Physiology, 2020)
Three-dimensional simulations of peripheral, deep venous flow during muscular exercise in limbs of healthy subjects and in those with venous dysfunction were carried out by a computational fluid-dynamics (CFD) approach using the STAR CCM+ platform. The aim was to assess the effects of valvular incompetence on the venous calf pump efficiency. The model idealizes the lower limb circulation by a single artery, a capillary bed represented by a porous region and a single vein. The focus is on a segment of the circuit which mimics a typical deep vein at the level of the calf muscle, such as the right posterior tibial vein. Valves are idealized as ball valves, and periodic muscle contractions are given by imposing time-dependent boundary conditions to the calf segment wall. Flow measurements were performed in two cross-sections downstream and upstream of the calf pump. Model results demonstrate a reduced venous return for incompetent valves during calf exercise. Two different degrees of valvular incompetence are considered, by restricting the motion of one or both valves. Model results showed that only the proximal valve is critical, with a 30% reduction of venous return during calf exercise in case of valvular incompetence: the net flow volume ejected by the calf in central direction was 0.14 mL per working cycle, against 0.2 mL for simulated healthy limbs. This finding appeared to be consistent with a 25% reduction of the calf ejection fraction, experimentally observed in chronic venous disease limbs compared with healthy limbs.